Relaxation Dynamics of Biomass-Derived Copolymers With Promising Gas-Barrier Properties - Sanz, Alejandro; Linares, Amelia; García-Gutiérrez, Mari Cruz; Nogales, Aurora; Paszkiewicz, Sandra; Zubkiewicz, Agata; Szymczyk, Anna; Ezquerra, Tiberio A. (Frontiers in Chemistry, 2022)
This article presents an experimental study on the relaxation dynamics of a series of random copolymers based on bio-friendly comonomers with interesting gas barrier properties. We analyze the relaxation response in the glassy and ultraviscous regime of poly (trimethylene furanoate/sebacate) random copolymers via dielectric spectroscopy. We report lower values of dynamic fragility [a dimensionless index introduced in 1985 (Angell, Relaxations in Complex Systems, 1985)] in comparison to popular polyesters widely used in industry, such as poly (ethylene terephthalate), suggesting that the amorphous phase of these furanoate-based polyesters adopt an efficient chain packing. This is consistent with their low permeability to gases. We also discuss on different equations (phenomenological and theory-based approaches) for fitting the temperature-evolution of the alpha relaxation time.